Removal Of Pharmaceutical Compounds Using Photocatalysis On Ferric Oxide Doped Titanium Dioxide - Affendi, Ahmad Zaid Ahmad (Universiti Sains Malaysia, 2022)
The presence of the micropollutants in the aquatic environment has caused significant concern in recent years. The occurrence of water pollution comes from the contamination of harmful substances that bring harm to human life, animals, and the environment. The present study uses Fe2O3-TiO2 nanocomposites as a photocatalyst to investigate the degradation efficiency of ATL, CBZ, and DIC in synthetic wastewater on a laboratory scale. The objectives of this study are twofold. Firstly, is to examine the effect of photocatalytic degradation of pharmaceutical compounds (ATL, CBZ, and DIC) using Fe2O3-TiO2. In an attempt to degrade the pharmaceutical compounds in synthetic wastewater, a synthesized Fe2O3 doped TiO2 photocatalyst with different dose loading was applied. Secondly, is to investigate the efficiency of recovered nanocomposite catalyst Fe2O3-TiO2 using different method after photocatalysis treatment. Results have shown that there was positive effect of photocatalytic degradation on the three PhCs (ATL, CBZ, and DIC) when using Fe2O3-TiO2 with different dose loading. Furthermore, using recovered nanocomposite catalyst Fe2O3-TiO2 by adopting method such as washed with water (H2O) and Hydrogen Peroxide (H2O2) have slightly similar results in removing the three PhCs (ATL, CBZ, and DIC) and able to reuse the recovered nanocomposite catalyst Fe2O3-TiO2 until 5 cycles.